Human Ace D/I Polymorphism Could Affect the Clinicobiological Course of COVID-19 - Aladag, Elifcan; Tas, Zahit; Ozdemir, Bilgesu Safak; Akbaba, Tayfun Hilmi; Akpınar, Meltem Gulsun; Goker, Hakan; Unalan-Altintop, Tugce; Inkaya, Ahmet Cagkan; Alp, Alpaslan; Metan, Gokhan; Haznedaroglu, Ibrahim Celalettin; Balci-Peynircioglu, Banu; et al. (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Introduction. The coronavirus disease 2019 (COVID-19), that is caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2), has spread rapidly worldwide since December 2019. The SARS-CoV-2 virus has a great affinity for the angiotensin-converting enzyme-2 (ACE-2) receptor, which is an essential element of the renin-angiotensin system (RAS). This study is aimed at assessing the impact of the angiotensin-converting enzyme (ACE) gene insertion (I)/deletion (D) polymorphisms, on the susceptibility and clinical outcomes of the COVID-19 immunoinflammatory syndrome. Patients and Methods. A total of 112 patients diagnosed with COVID-19 between 1 and 15 May 2020 were enrolled in the study. ACE gene allele frequencies were compared to the previously reported Turkish population comprised of 300 people. Results. The most common genotype in the patients and control group was DI with 53% and II with 42%, respectively. The difference in the presence of the D allele between the patient and control groups was statistically significant (67% vs. 42%, respectively, p<0.0001). Severe pneumonia was observed more in patients with DI allele (31%) than DD (8%) and II (0%) (p=0.021). The mortality rate, time to defervescence, and the hospitalization duration were not different between the genotype groups. Conclusion. Genotype DI of ACE I/D polymorphism is associated with the infectious rate particularly severe pneumonia in this study conducted in the Turkish population. Therefore, ACE D/I polymorphism could affect the clinical course of COVID-19.